2004
DOI: 10.1086/422396
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of theSchistosoma mansoni–Specific Immune Responses Elicited by Treatment with Praziquantel in Ugandans with HIV‐1 Coinfection

Abstract: We show that Ugandan adults coinfected with Schistosoma mansoni and human immunodeficiency virus type 1 (HIV-1) are able to mount S. mansoni-specific immune responses but that few such responses increase after treatment with praziquantel (PZQ). Levels of soluble worm antigen (SWA)-specific immunoglobulin (Ig) G1, IgG2, IgG3, IgG4, interleukin (IL)-4, and IL-5 increased significantly in HIV-negative participants after treatment with PZQ, whereas most soluble egg antigen-specific antibody responses and levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…These boosts in antibodies at six weeks post-treatment were consistent with those observed at five weeks post-treatment [36], three months post-treatment [37] and at six months post-treatment [27] among S. mansoni infected non-pregnant individuals in endemic areas. Similar increases in antibodies were recently reported following treatment among non-pregnant adults from a new focus of S. mansoni infection [38].…”
Section: Discussionsupporting
confidence: 81%
“…These boosts in antibodies at six weeks post-treatment were consistent with those observed at five weeks post-treatment [36], three months post-treatment [37] and at six months post-treatment [27] among S. mansoni infected non-pregnant individuals in endemic areas. Similar increases in antibodies were recently reported following treatment among non-pregnant adults from a new focus of S. mansoni infection [38].…”
Section: Discussionsupporting
confidence: 81%
“…It is believed that such treatment-induced responses may be useful in generating protective antischistosomal immunity [9,25]. Studies have demonstrated that HIV-1 infection suppresses posttreatment cytokine responses, which may partly explain increased reinfection rates among HIV-1-infected adults [14,26,27]. In this study, concentrations of SWA-specific IL-5 and IL-13 and SEA-specific IL-5 increased significantly after treatment, as did the proportion of subjects with detectable SWA-specific IL-4, IL-5, and IL-13 and SEA-specific IL-5 responses; the absence of significant increases in posttreatment SEA-specific IL-4 and IL-13 responses may partly reflect smaller numbers of subjects but does accord with findings in HIV-1-negative subjects [9].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be a real effect of HIV-1 immunosuppression. Data showing failure to augment antibody responses in HIV-1-infected subjects suggest that some posttreatment type 2 responses are impaired [14]; presumably, mechanisms of eosinophil proliferation independent of-or requiring higher levels of-type 2 cytokines explain this impaired eosinophil production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest that this may lead to more rapid progression of HIV infection should a previously HIV-negative individual with schistosomiasis become infected with HIV. After treatment with praziquantel, HIV-positive Ugandans were unable to mount S. mansoni specific immunological responses, which may partly explain their increased susceptibility to reinfection [58].…”
Section: Schistosomiasismentioning
confidence: 99%